Load-sensitivity of regional tissue deformation in the right ventricle: isovolumic versus ejection-phase indices of contractility. Issue 4 (8th August 2007) - Missant, C; Rex, S; Claus, P; Mertens, L; Wouters, P F
Abstract : Objective: Doppler myocardial imaging is increasingly being used to evaluate regional and global cardiac function. Quantitative measurements of tissue deformation obtained during ejection as well as isovolumic contraction have been proposed as new indices of contractility; however, their load-sensitivity remains a matter of controversy. Maximum strain rate (SRmax ) and isovolumic strain acceleration (ISAmax ) were compared with regard to sensitivity for inotropic state, heart rate and loading conditions in the right ventricle (RV), using pressure-volume analysis as the reference method. Design: Prospective animal study. Setting: University hospital laboratory. Interventions: RV contractility was measured at baseline, after inotropic modulation with esmolol and dobutamine, at different atrial pacing rates and during controlled alterations of RV preload and afterload. Main outcome measures: RV contractility was assessed with the slope (Mw) of preload recruitable stroke work and longitudinal SRmax and ISAmax . Results: SRmax and ISAmax reflected the drug-induced changes in contractility, while only ISAmax increased with higher pacing rates. Acute lowering of RV preload did not affect either of the indices studied. In contrast, an increase in RV afterload consistently decreased SRmax (from 1.05 (SD 0.41) to 0.73 (SD 0.26) s -1, p = 0.03) but had variable effects on ISAmax and Mw. However, a significant correlation was found between proportional changes in ISAmax and Mw during high-afterload conditions (r2 = 0.89, p = 0.005). Conclusions: Both SRmax and ISAmax reflected changes in RV contractility. ISAmax was less sensitive to changes in RV afterload than SRmax and may therefore be a more robust index of global RV contractility.